Distribution of Lymantria disparin forests of CSI «Kyzylzharskoe forestry» of the North Kazakhstan region - Kozhevnikova, L.N.; Levykh, A.Yu.; Panchenko, V.Yu. (Fundamental and Experimental Biology, 2018)
Lymantria disparis one of the most dangerous, widespread forest pests. In most of its range this species gives periodic outbreaks of mass reproduction. Its polyphage caterpillars can eat about 300 plant species, but they cause special damage to birch plantations. Based on this, a number of studies on the distribution of the Lymantria disparhave been conducted in the Kyzylzharskoye forestry in the North Kazakhstan region: ac-counting, collection, analysis of all stages of pest development. Repeated outbreaks of pest activity were identified in researching territory in 3 zones: minor damage zone (the occurrence of foci less than 30 %), periodic intensive damage zone (31–70 %) and permanent damage (more than 70 %). Also pointed that prolonged drought for several years has a great influence on the duration of outbreaks of Lymantria disparmass reproduction. It confirmed by our records of increasing amount of pests in 2016 and 2017 years. With the aim of exterminating the pest and reducing the foci of infection of birch plantings with Lymantria dispar, CSI «Kyzylzharskoe forestry» carried out forest treatment with the biological preparation «Hercules–48 %». This drug belongs to the 3rd class of danger and is safe for people, warm-blooded animals, birds, bees and useful entomofauna.